2008
DOI: 10.1111/j.1460-9568.2008.06172.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between neuropeptide Y (NPY) and brain‐derived neurotrophic factor in NPY‐mediated neuroprotection against excitotoxicity: a role for microglia

Abstract: The neuroprotective effect of neuropeptide Y (NPY) receptor activation was investigated in organotypic mouse hippocampal slice cultures exposed to the glutamate receptor agonist alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA). Exposure of 2-week-old slice cultures, derived from 7-day-old C57BL/6 mice, to 8 microm AMPA, for 24 h, induced degeneration of CA1 and CA3 pyramidal cells, as measured by cellular uptake of propidium iodide (PI). A significant neuroprotection, with a reduction of PI upta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 61 publications
1
40
0
Order By: Relevance
“…3,4 NPY actions are mediated by G protein-coupled receptors, which have been named NPY Y 1 , Y 2 , Y 4 , Y 5 , and y 6 . 3,5 NPY is expressed in the retina of mammals and nonmammals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 NPY actions are mediated by G protein-coupled receptors, which have been named NPY Y 1 , Y 2 , Y 4 , Y 5 , and y 6 . 3,5 NPY is expressed in the retina of mammals and nonmammals.…”
Section: Resultsmentioning
confidence: 99%
“…3,5 NPY is expressed in the retina of mammals and nonmammals. [6][7][8][9][10][11][12] In rodent retinas, NPY-immunoreactivity (NPY-ir) is present in the inner retina, it is localized in cell bodies at both inner nuclear layer (INL) and ganglion cell layer (GCL), and is also present in processes located in the inner plexiform layer (IPL).…”
Section: Methodsmentioning
confidence: 99%
“…BDNF, administered in vitro (Nawa et al, 1993) or in vivo (Nawa et al, 1994), induces an increase in NPY mRNA and peptide content. Xapelli et al (2008) reported that the expression of NPY in the hippocampus is under the control of BDNF receptor activity. Neurotrophins, and particularly BDNF, are known to modulate many aspects of neuronal plasticity (Shieh and Ghosh, 1999;Thoenen, 2000) and the selection of functional neuronal connections in the CNS (Huang and Reichardt, 2001;Mamounas et al, 2000;Poo, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that BDNF enhanced an expression of NPY in the striatum, cortex and the hippocampus (Barnea & Roberts, 2001;Barnea et al, 2004;Nawa et al, 1994;Reibel et al, 2000;Takei et al, 1996;Wirth et al, 2005;Yoshimura et al, 2009). In the mouse organotypic hippocampal slice cultures exposed to glutamate receptor agonist, degeneration of CA1 and CA3 pyramidal neurons was diminished by Y2 receptor agonist and such protection strongly inhibited the stimulating effect of AMPA on the BDNF level (Xapelli et al, 2008). It was also found that NPY treatment decreased BDNF and increased nerve growth factor production in the rat hypothalamus (Gelfo et al, 2011).…”
Section: How Does Npy Modulate Neurodegenation and Neuroprotection?mentioning
confidence: 65%
“…The activation of Y1 receptors produced neuroprotective effects in kainate excitotoxicity model of rat organotypic hippocampal slice cultures (Xapelli et al, 2007) and in methamphetamine neurotoxicity model in the mouse striatum (Thieriet et al, 2005), but in both models Y1R had a little weaker effect than Y2R agonists. Excitotoxicity induced by AMPA in organotypic mouse hippocampal slice cultures showed that AMPA-induced degenerations of CA1 and CA3 pyramidal neurons were strongly inhibited by Y2 but not Y1 or Y5 receptor agonists (Xapelli et al, 2008). More detailed studies in hippocampal slices have shown that neuroprotective properties of a particular Y receptor may depend on the region where the receptor is located.…”
Section: The Role Of Particular Y Receptors In Neuroprotectionmentioning
confidence: 99%